(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The work is devoted to the study of carbon-hydrolyzing enzymes of soil micromycetes isolated from various natural sources in the Republic of Uzbekistan. Among the study of cellulolytic and xylanolytic enzymes of more than 150 fungal cultivations, surface-active fungi were selected in an amount of 78, belonging to the genera Aspergillus, Coriolus, Eupenicillium, Fusarium, Penicillium, Sporotrichum, Trichoderma, and Verticillium. Further, by deepening the experiments by the methods of deep cultivation on polysaccharide-containing media, the most active fungi were detected in an amount of -28, belonging to the genera Aspergillus (8 cultivations), Fusarium (7 cultivations), Penicillium (5 cultivations), and representatives of saprophytic fungi, Alternaria (5 cultivations), Acremonium (2 cultivations), and Ulocladium (1 cultivation). The study of cellulolytic, xianolytic activity, the accumulation of proteins by selected fungi on a medium with different concentrations of microcrystalline cellulose introduced into the medium as the sole carbon source, showed fungi are capable of producing cellulases that actively hydrolyze carboxymethyl cellulose, cotton, and wood pulp in as little as 10-30 minutes. It was established that the manifestation of fungal activity depends on the composition of the nutrient medium, cultivation time, species and concentration of substrates, and species affiliation of the fungi. The identified producers of carbon-hydrolyzing enzymes of soil micromycetes are promising sources of biotechnological products by enzymatic catalysis of various cellulose- and hemicellulose-containing wastes.